STATUS PENGGUMPALAN (AGREGASI) TROMBOSIT SEBAGAI FAKTOR PROGNOSTIK TEJADINYA KELUARAN KLINIS STROK INFARK MENDADAK (STROK INFARK AKUT) - Linda Rosita; Usi Sukorini; Budi Mulyono (Indonesian Association of Clinical Pathologist and Medical laboratory, 2011)
The propriate management of acute infarction stroke will be able to reduce the morbidity and mortality of the disease. In diagnosingand managing the diseases, for the detection of the risk or prognostic factors information’s such as the history physical findings,confirmation and other supporting tests are needed. One of the supporting test is the laboratory examination i.e. platelet aggregationtest. Platelet aggregation is suggested having an important role in haemostasis especially to prevent excessive bleeding by forming plateletplug. Finally, further hyperactivity of platelet in terms of platelet hyper aggregation can create a thrombus and moreover lead to obstructthe vessels. The occlusion will give a negative outcome of an acute infarction stroke. The aim of this study is to know whether platelethyper aggregation has a contribution in the outcome of the disease or not by certain testing. A prospective cohort study was carried out,to compare between two groups of exposed and non-exposed group in Sardjito hospital Yogyakarta during the period of March up toearly July 2007. Eighty four subjects who met the inclusion and exclusion criteria were involved in this study. The exposed group was agroup of acute infarction stroke patient who were exposed to platelet hyper aggregation 48 (57%), on the other hand, patients who didnot have platelet hyper aggregation was separated as non-exposed group is 36 (43%). Inception of cohort was applied when the patientwas admitted to the emergency unit during 72 hours of the onset, before receiving antithrombotic drugs and had no previous history ofstroke. The patients were followed after 7 days hospitalization in the stroke unit and neurology unit and the outcome was measured byevaluating the score using Gadjah Mada stroke scale. The characteristics of the subjects were grouped by baseline data X2 test. Unvariedanalysis and multivariate analysis were taken to get the relative risk of having acute infarction stroke. In this case logistic regressionanalysis was used to know the relative risk (RR) measurement. Prognostic factors had influenced the outcome of acute infarction strokein patients who had a history of cardiovascular disease and aggregation status. The outcome of the platelet hyper aggregation grouphad a RR=2.15 (95% CI: 2.01–4.07) and the history of cardiovascular disease had a RR=1.78 (95% CI: 1.18–13.28).